慢性肾病与卒中的因果关系：一项两样本双向孟德尔随机化研究Causality between Chronic Kidney Disease and Stroke: A Two-Sample Bidirectional Mendelian Randomization Study - 宋金云，赵宏宇 (SONG Jinyun, ZHAO Hongyu ) (Zhongguo cuzhong zazhi)
目的 采用两样本双向孟德尔随机化（Mendelian randomization，MR）方法分析慢性肾病（chronic kidney disease，CKD）与卒中之间的因果关系。 方法 正向研究以CKD为暴露因素，卒中为结局变量，获取CKD和卒中的全基因组关联分析数据，筛选出与CKD显著相关的单核苷酸多态性（single nucleotide polymorphism，SNP）作为工具变量。反向研究则筛选与卒中密切相关的SNP作为工具变量，CKD作为结局变量。使用逆方差加权法、加权中位数法和MR-Egger回归法进行双向MR分析，探讨CKD与卒中的因果关系。通过Cochran’s Q检验评估异质性，MR-Egger回归截距项进行多效性检验以及留一法进行敏感性分析，以评估MR结果的稳健性。 结果 正向研究共获得4个与CKD显著相关的SNP作为最终的工具变量，逆方差加权法结果显示CKD与卒中之间具有显著的正向因果关系（OR 1.123，95%CI 1.051～1.200，P＜0.001）。反向MR结果显示，卒中也会增加CKD的发生风险（OR 1.213，95%CI 1.003～1.466，P=0.046）。未发现异质性和水平多效性（均P>0.05），逐个剔除SNP后，MR分析结果稳健。 结论 CKD与卒中存在双向因果关系，CKD会增加卒中的风险，而卒中也会增加CKD的发生风险。 Abstract: Objective Two-sample bidirectional Mendelian randomization (MR) method was used to analyze the causality between chronic kidney disease (CKD) and stroke. Methods With CKD as the exposure factor and stroke as the outcome variable, the forward study obtained the genome-wide association study data for CKD and stroke, and screened out the single nucleotide polymorphisms (SNPs) significantly associated with CKD as instrumental variables. The reverse study screened SNPs closely related to stroke as instrumental variables, with CKD as the outcome variable. Inverse variance weighted, weighted median, and MR-Egger regression were used for bidirectional MR analysis to explore the causality between CKD and stroke. Heterogeneity was evaluated using Cochran’s Q test, pleiotropy was tested using the intercept term of MR-Egger regression, and sensitivity analysis was performed using the leave-one-out to evaluate the robustness of the MR results. Results In the forward study, four SNPs significantly correlated with CKD were obtained as the final instrumental variables, and the results of inverse variance weighted showed a significant positive causality between CKD and stroke (OR 1.123, 95%CI 1.051-1.200, P＜0.001). Reverse MR results showed that stroke also increased the risk of CKD (OR 1.213, 95%CI 1.003-1.466, P=0.046). No heterogeneity or horizontal pleiotropy was found (both P>0.05) , and the results of MR analysis were robust after removing SNPs one by one. Conclusions Bidirectional causality was observed between CKD and stroke. CKD increases the risk of stroke, and stroke also increases the risk of CKD.